INSENTIF PASAR MODAL UNTUK MANAJEMEN LABA - Lodovicus Lasdi (Journal of Management and Business, 2006)
Regulator and practitioner believe that earning management have pervasive and problematic in nature, while research academics not yet indicated that the earning management have the great influence to reported earning, or warn the investor for the attention to earning management. To obtain the same perception between academician, practitioner and regulator and also answer the question addressed to regulator, hence needed a clearer definition about earning management, and capital market incentive for earning management. Without a clear definition, hence identify the earning management can only conducted hereafter the happening of. Academic researcher better more amount giving its attention at capital market incentive for earning management. The increasing of assessment on stocks market, making sensitive manager progressively by level of company stock price and its relation with the accounting number (profit). As a result, manager has an incentive to manage the profit to maintain and improve the stock valuation.